Systemic antibiotic prophylaxis in arthroplasty – a narrative review of how many doses are optimal - Peter Wahl; Philip Drennan; Michel Schläppi; Yvonne Achermann; Michael Leunig; Emanuel Gautier; Emanuel Benninger (EFORT Open Reviews)
Systemic antibiotic prophylaxis (SAP) is well-established in arthroplasty to prevent periprosthetic joint infection. However, the optimal duration and dosing of SAP remain a matter of debate, as evidenced by ongoing discordance between recommendations and clinical practice, reflected in the heterogeneity and imprecision of national and societal guidelines. The evidence currently available regarding the duration of SAP is summarised and discussed, specifically the postoperative repeated administration of antimicrobials within the first 24 h. The evidence available suffers from limitations, specifically deficiencies in outcome assessments in the available randomised controlled trials. Observational studies suggest that a short postoperative prolongation (<24 h) of SAP in arthroplasty may result in superior long-term outcomes compared to a single dose, and that an optimal dosing strategy, which warrants further prospective evaluation, may involve ‘stacked dosing’ in the early postoperative period, with re-administration every two half-lives when using commonly recommended beta-lactam antibiotics, instead of repetition at usual dosing intervals over 24 h. A stacked approach would also cover recognised indications for repetition, such as major blood loss and increased duration of operation, potentially simplifying prescribing protocols. Pharmacokinetic simulations are provided to illustrate the distinct concentration–time profiles associated with different prophylaxis regimens. Prolonging SAP beyond 24 h is not recommended. This review concludes by providing recommendations for further research, particularly a call to document SAP regimens with sufficient detail (choice of drug, dose regimen, and duration of administration) into established national arthroplasty registries, which should rapidly enable a significantly more nuanced understanding of these critical issues than permitted by the current literature.